Copredication, Davidson and Logical Form - Molto, Daniel (Logic and Logical Philosophy, 2023)
This paper offers a novel account of polysemous copredicative sentences. The solution, which it is argued enjoys a number of advantages over the alternative accounts currently on the market, is inspired by Donald Davidson’s first attempt to deal with ambiguity. Specifically, the account involves mapping ambiguities in the object language (in this case polysemous singular terms) onto ambiguities in the metalanguage. If this account is coherent and superior to its rivals, it tells us something important about logical form: the value of logical form does not lie in the elimination all lexical ambiguity.